2010
DOI: 10.1007/s10689-010-9383-0
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the communication preferences regarding genetic testing in individuals from families with identified breast/ovarian cancer mutations

Abstract: The responsibility for informing at-risk relatives of the availability of genetic testing for breast/ovarian cancer gene (BRCA1 or BRCA2) mutations currently falls on the probands. This study explored the support needs of individuals from families with identified BRCA1 or BRCA2 mutations when communicating about genetic risk and genetic testing with at-risk family members. Thirty-nine semi-structured telephone interviews were conducted with individuals from families with identified BRCA mutations. Interview re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
5
33
0
Order By: Relevance
“…In terms of the effect of gender on familial risk communication, we found conflicting results. For the entire sample we found no gender difference, which is consistent with some of the previous research on communication of hereditary cancer syndrome risk (Aktan-Collan et al, 2011;Ishii et al, 2011;McGivern et al, 2004;Patenaude et al, 2006;Ratnayake et al, 2011;Stoffel et al, 2008;Vos et al, 2011). However, our findings from the regression analysis showed that women were more likely than men to have communicated with all their at-risk relatives.…”
Section: Predictors Of Family Communicationsupporting
confidence: 90%
“…In terms of the effect of gender on familial risk communication, we found conflicting results. For the entire sample we found no gender difference, which is consistent with some of the previous research on communication of hereditary cancer syndrome risk (Aktan-Collan et al, 2011;Ishii et al, 2011;McGivern et al, 2004;Patenaude et al, 2006;Ratnayake et al, 2011;Stoffel et al, 2008;Vos et al, 2011). However, our findings from the regression analysis showed that women were more likely than men to have communicated with all their at-risk relatives.…”
Section: Predictors Of Family Communicationsupporting
confidence: 90%
“…Several studies stressed that transmission of genetic risk information depends on a variety of individual, social, and situational factors (Forrest et al, 2003;Gaff et al, 2005;Keenan et al, 2005;Mesters et al, 2005;Ratnayake et al, 2011). "Feelings" of being responsible for the well-being of others or even anticipated feelings of regret for causing harm were strong facilitators for disclosure.…”
Section: Disclosure (B2)mentioning
confidence: 99%
“…32,33 Family communication barriers are also likely to limit mutation spreading within families in the clinic 34 and research environment. 35 If these barriers were identified and addressed early, family members could serve as advocates for each other's health and improve genetic testing uptake in disinclined family members. Improving family communication is challenging, but work in this area is promising.…”
Section: Discussionmentioning
confidence: 99%